Study of the lipid fraction of Moroccan and Italian carobs (Ceratonia siliqua L.) - Amar, Yasmine M. Ben; Potortì, Angela G.; Albergamo, Ambrogina; Litrenta, Federica; Rando, Rossana; Mouad, Lahkim B.; Brigui, Jamal; Chouaibi, Noureddine; Di Bella, Giuseppa (European journal of lipid science and technology, 2024)
Carob (Ceratonia siliqua L.) is a characteristic fruit from the Mediterranean area, composed of a hard pulp and numerous seeds that have been unfairly undervalued and underutilized over time. To enhance the Mediterranean's biodiversity and support food production from sustainable resources, the carob has recently received attention for its nutritional value, and it has advantageously served as a healthy ingredient of many food products. Hence, in this study, the composition of the Mediterranean carob was further deepened by investigating its lipid fraction on a dry weight basis in relation to the fruit part (i.e., pulp and seeds) and the geographical origin (i.e., different Moroccan and Italian provinces). On average, lipids of pulp and seeds amounted to 1.71% and 2.46%, respectively. Predominant fatty acids were palmitic, oleic, and linoleic acids. Palmitic and oleic acids were higher in pulp (20.21%–26.50% and 37.63%–44.49%) than seeds (13.93%–17.26% and 31.92%–36.66%), whereas linoleic acid showed an opposite accumulation trend (pulp: 8.32%–15.46%, seeds: 38.19%–43.45%). Among sterols, β‐sitosterol (57.49%–72.47%), Δ‐5‐avenasterol (10.26%–21.27%), and stigmasterol (3.97%–8.11%) accounted for more than 70% of total sterols of pulp, whereas β‐sitosterol alone represented more than 70% of sterols in seeds. Considering tocopherols, γ‐tocopherol was the most abundant isomer both in pulp (10.37–22.78 mg/100 g) and seeds (4.95–22.86 mg/100 g). Carob also resulted in a good source of squalene, which on average was 2.17 mg kg−1 in pulp and 19.07 mg kg−1 in seeds. A principal component analysis pointed out that the study of the lipid fraction of carob can help in discriminating samples based on their Moroccan or Italian origin. Practical Applications: The study provides further insights into the still‐little‐explored lipid fraction of Mediterranean carob and fills a relevant gap in the literature by contributing to a more exhaustive framework of the nutritional and functional value of this fruit. In a wider perspective, it can be of practical help in the formulation of carob‐based products and in the establishment of a more informed market of carob and carob‐based products. Graphical : Maroccan and Sicilian carobs were investigated for their lipid profiles using advanced analytical techniques and statistical tools. A favorable FA composition and beneficial amounts of minor compounds with bioactive properties marked the Mediterranean carobs. Additionally, findings were discussed in relation to the fruit part and geographical origin.